Measurement of pulmonary gas exchange variables and lactic anaerobic capacity during field testing in elite indoor football players - Angius, L.; Cominu, M.; Filippi, M.; Piredda, C.; Migliaccio, G. M.; Pinna, M.; Milia, R.; Tocco, F.; Concu, A.; Crisafulli, A. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The aims of this study were: 1) to examine the gas exchange responses of elite indoor football players to a repeated sprint ability (RSA) test; and 2) to verify whether or not the excess of carbon dioxide production (CO2excess) correlates with blood lactate accumulation during RSA field testing. Methods: Eleven elite male indoor football players were recruited. A preliminary incremental exercise test on a treadmill was performed to elicit V`O2max. Then, participants underwent an RSA test consisting in a shuttle running through a course with various changes of direction while wearing a portable gas analyzer able to provide values of oxygen uptake, carbon dioxide production, and CO2excess. BLa concentrations during recovery were also measured. Results: The main results were that: 1) during the RSA test subjects did not reached the V`O2max level achieved in the preliminary test; 2) during the RSA test BLa levels were higher compared with the preliminary test; 3) the peak BLa concentration during recovery was significantly correlated with the average CO2excess Conclusion: It was concluded that the RSA test did not appear to be useful to elicit V`O2max. Rather, it seemed suitable to recruit subjects` lactic anaerobic capacity. Moreover, CO2excess appeared suitable for qualitatively estimate BLa accumulation during field testing.